Study on the Dynamic Performance of Joint Mechanism with Considering Oil Film Lubrication Clearance - Wang Xupeng; Liu Geng; Ma Shangjun; Tong Ruiting (Jixie chuandong)
In order to study the dynamic performance of mechanism with lubricated clearance joint,an improved transition force model is established,accounts for not only squeeze-film effects,but also wedge-film effects,and is applicable to both long and short bearings. Then,taking the planar slider-crank mechanism with lubricated clearance joint as study object,through the analyzing and comparing of two working conditions of dry friction and lubrication,the rationality of the new model is verified. At the same time,through the simulation analysis of the different clearance values,the influence law of the clearance values on the dynamic performance of joint mechanism with lubrication clearance is studied. The study results show that,comparing with the working condition of dry friction,when considering the joint lubrication,the acceleration oscillation phenomenon of the mechanism is effectively suppressed,the dynamic performance is improved significantly. At the same time,with the increase of clearance size,the simulation results with lubrication appear deviation in the dead position of mechanism,and the more clearance size,the more obvious deviation,but the deviation is significantly less than that of dry contact clearance joint.